PENERAPAN INTERNATIONAL FINANCIAL REPORTING STANDARD TERHADAP MANAJEMEN LABA DI INDONESIA - Sanjaya, Ida Bagus Wira; Ulupui, I Gusti Ketut Agung (E-Jurnal Akuntansi, 2016)
The purpose of this study was to determine the difference between the earnings management practices before and after adopting IFRS on the type of manufacturing companies, and to determine the difference between the earnings management of manufacturing companies classified as large and small. The data used in this research is secondary data obtained from the annual reports of the companies listed at Indonesia Stock Exchange in 2010-2013 which is accessed directly via the website www.idx.co.id. The population is manufacturing companies listed in Indonesia Stock Exchange in 2010-2013. The sample selection using purposive sampling method and obtained a sample of 62 companies. This research is a comparative research were performed by using test Willcoxon. From the test results showed that there are differences in earnings management practices significantly between before and after adopting IFRS as well as the difference between the earnings management manufacturing companies classified as large and small.
Keywords: Earnings Management, International Financial Reporting Standard (IFRS), Manufacturing Company, Comparative Research